Revisiting the 'cornerstone of Amazonian conservation': a socioecological assessment of Brazil nut exploitation - Guariguata, Manuel R.; Cronkleton, P.; Duchelle, Amy E.; Zuidema, Pieter A. (Springer, 2017)
The Brazil nut (the seeds of the rainforest tree Bertholletia excelsa) is the only globally traded seed collected from the wild by forest-based harvesters across the Amazon basin. The large geographic scale of Brazil nut exploitation and the significant contributions to local livelihoods, national economies, and forest-based development over the last decades, merit a review of the "conservation-through-use" paradigm. We use Elinor Ostrom's framework for assessing sustainability in socioecological systems: (1) resource unit, (2) users, (3) governance system, and (4) resource system, to determine how different contexts and external developments generate specific conservation and development outcomes. We find that the resource unit reacts robustly to the type and level of extraction currently practiced; that resource users have built on a self-organized system that had defined boundaries and access to the resource; that linked production chains, market networks and informal financing work to supply global markets; and that local harvesters have used supporting alliances with NGOs and conservationists to formalize and secure their endogenous governance system and make it more equitable. As a result, the Brazil nut model represents a socioecological system that may not require major changes to sustain productivity. Yet since long-term Brazil nut production seems inextricably tied to a continuous forest cover, and because planted Brazil nut trees currently provide a minimal contribution to total nut production basin-wide, we call to preserve, diversify and intensify production in Brazil nut-rich forests that will inevitably become ever more integrated within human-modified landscapes over time.